Anti-anxiety Properties of Selected Medicinal Plants - Khan, Asmatullah; Akram, Muhammad; Thiruvengadam, Muthu; Daniyal, Muhammad; Zakki, Shahbaz A.; Munir, Naveed; Zainab, Rida; Heydari, Mojtaba; Mosavat, Seyed Hamdollah; Rebezov, Maksim; Shariati, Mohammad Ali (Current Pharmaceutical Biotechnology, 2022)
Exploration of new drugs targeting anxiety treatment is a major concern worldwide. Medicinal plants are being used as a potential source of novel drugs for anxiety disorders. The objective of this review is to provide information about the healing outcomes of anxiety treatment with natural products. Valeriana officinalis, Citrus aurantium, Commelina benghalensis, Achyranthes aspera, Mimosa pudica, Achillea millefolium, Nymphaea alba, Leonurus cardiac, Camellia sinensis, Turnera aphrodisiaca, Crataegus oxyacantha and Piper methysticum showed promising effects on anxiety in animal models. In clinical studies, passion flower, kava, valerian, St John's wort, and hwagandha showed the most positive results. More studies are needed for the exploration of the antianxiety of medicinal plants. In drugs derived from natural sources have explored many components that are playing an essential role in curing anxiety disorders and associated complications.
Keywords: Anxiety